PENGARUH PENDEKATAN SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS (STEM) TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN LITERASI SAINS SISWA SEKOLAH DASAR - Wulandari, Ika; Anggoro, Subuh; Dyah Purwandari, Ristiana; Gunawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesia's education still faces serious challenges in developing 21st-century skills, as reflected in the 2022 PISA results, where Indonesia ranked 69th out of 80 countries with reading, mathematics, and science scores below the OECD average. At SD Negeri 2 Darmayasa, Pejawaran, Banjarnegara, 60% of fifth-grade students struggled to understand the water cycle due to its abstract nature and the limited use of contextual, visualized learning media. This study aimed to examine the effect of the Science, Technology, Engineering, and Mathematics (STEM) approach on elementary students' critical thinking and science literacy. A quantitative approach with a Quasi-Experimental Nonequivalent Control Group Design was employed, involving 31 fifth-grade students from two schools in Gugus Sudirman selected through cluster random sampling: 19 students as the experimental group, taught using STEM through Project-Based Learning on the water cycle, and 12 students as the control group, taught conventionally. Data were collected through essay tests and analyzed using independent sample t-tests and Pearson correlation with SPSS 25. Results showed that the STEM approach had a significant effect on both critical thinking (p = 0.000, mean difference = 14.82) and science literacy (p = 0.000, mean difference = 20.67). However, the correlation between critical thinking and science literacy in the experimental group was positive but weak and not statistically significant (r = 0.413, p = 0.079). These findings suggest that STEM effectively enhances critical thinking and science literacy separately, although their development does not necessarily occur in parallel within individual students.